Optimization of culture conditions for squalene production and squalene extraction method of Thraustochytrium sp. TN22 - Hien, Hoang Thi Minh; Thom, Le Thi; Ha, Nguyen Cam; Anh, Hoang Thi Lan; Hong, Dang Diem (Academia Journal of Biology, 2020)
Squalene, a natural triterpene with important roles as antioxidant, skin hydrating, cardio-protection and detoxifier, has attracted the attention of researchers in the world. This study investigated the optimal culture conditions for squalene production and to develop a method for squalene extraction and purification from cell suspension of Thraustochytrium sp. TN22. The results showed that squalene production by the strain Thraustochytrium sp. TN22 was optimum at 2% glucose, 0.5% yeast extract and 0,14% mixture of vitamins (B1, B6 and B12) at 28 oC for 2 days of cultivation. At the optimum conditions, the dry biomass, squalene content and productivity were approximately 9.3 g/L, 9.9 mg/g DCW and 95.3 mg/L, respectively. Time-dependence on cell lysis and extraction solvents were selected as the extraction parameters. The obtained results showed that the highest squalene production of 178.1 mg/100 g biomass was obtained in cell lysate at alkaline medium (pH = 10), at 60 oC for 6 hours and n-hexan was the best solvent for squalene extraction. Squalene was then purified on silica gel column using n-hexan as the mobile phase and 90% purity of squalene was archived. Our obtained results are promising for the commercial productions of various value-added compounds from species belong to the genus Thrautochytrium in Vietnam.